AUTONOMOUS LEARNING STRATEGY OF THE SUCCESSFUL NONTRADITIONAL STUDENTS - Siti Zulaihah; Ratri Harida (Eltin Journal : Journal of English Language Teaching in Indonesia, 2017)
Most students of English Education Program in STKIP PGRI Ponorogo can be considered as nontraditional students with family, work, and other life responsibilities which have many influences on their educational goals. Autonomous learning is a customized way of learning applied by individual to find out his own learning needs and learning goals, decide the most appropriate way for his own learning, as well as to monitor and evaluate the learning progress. This research used qualitative descriptive method. The primary techniques in data collection were questionnaire, and interview. In general, the most influential motivation for the students was internal motivation. Advisor’s availability, text book, internet, supportive atmosphere, self discipline, cozy and quiet place, and early morning were among the students’ choices for their autonomous learning. They frequently used music, film, video, essay, and smart phone application in their study. In general, the nontraditional students with high achievement were often felt easy to understand the material especially when it was delivered in relatively “easy” language, expressed their opinion bravely, and patient in doing their tasks. They considered friends, best friends, and lecturer as people who were capable to help them in doing autonomous learning